2014
DOI: 10.1007/s11695-014-1191-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Intragastric Balloon MedSil® on Weight Loss, Fat Tissue, Lipid Metabolism, and Hormones Involved in Energy Balance

Abstract: BackgroundThe prevalence of obesity continues to increase worldwide. Because obesity is associated with a number health-related problems as well as a shortened life span, treating obesity is an important clinical concern. Although various treatments are currently available, many are not efficacious in the long term. Therefore, additional medical treatment options for morbidly obese individuals must be explored. In this study, we examined the effects of the intragastric balloon MedSil® on anthropometric measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 37 publications
(42 reference statements)
6
33
0
Order By: Relevance
“…In particular, there were no aspiration events during swallowing, small bowel obstructions during balloon passage, or evidence of ulcers. The nausea, vomiting, and abdominal cramps reported here was similar to previous studies on liquid-filled gastric balloons even though no prophylactic anti-emetic medications were administered [3,11].…”
Section: Discussionsupporting
confidence: 87%
“…In particular, there were no aspiration events during swallowing, small bowel obstructions during balloon passage, or evidence of ulcers. The nausea, vomiting, and abdominal cramps reported here was similar to previous studies on liquid-filled gastric balloons even though no prophylactic anti-emetic medications were administered [3,11].…”
Section: Discussionsupporting
confidence: 87%
“…A few studies have analyzed the body composition after 6 months of IGB using bioelectrical impedance, showing a significant reduction in fat mass and fat-free mass [24, 46, 47]. Bužga et al used DXA to verify the body composition after treatment with IGB and demonstrated sharp decreases in fat and lean mass [48]. Our patients also presented similar changes in body composition verified by DXA.…”
Section: Discussionsupporting
confidence: 68%
“…Subsequently, the levels of ghrelin decreased but were still above baseline. Leptin significantly decreased, and the levels of adiponectin did not differ significantly (Buzga et al 2014).…”
Section: Intragastric Balloonmentioning
confidence: 85%